How Can Transactional Semantics Enhance the Commit Rate of Context-aware Service Composition in Advanced Pervasive Systems? - Widad Ettazi (International Association of Online Engineering (IAOE), 2021)
Context-aware composition of services exhibiting transactional properties poses several challenges. A major challenge is the transactional behavior of candidate services which is subject to perpetual change while the composition is running. Compositions of services displaying transactional properties must be dynamically adapted at run time to cope with context fluctuations. By dynamic adaptation, we refer to the ability to alter the composition behavior in response to changes affecting its execution. We focus on changes impacting the successful commit rate of transactional service composition. This has led us to explore the trail of a flexible homeomorphism between alternative behaviors. We propose a behavioral adaptation approach that adjusts the behavior of transactional compositions of services in a proactive and transparent manner. This strategy is based on the Profiled Task Class concept. A service composition generator has also been developed for the performance evaluation of components implementing the behavioral adaptation strategy in order to identify its impact on the commit rate of CATS compositions.